Investigating the possible usage of elephant grass ash to manufacture the eco-friendly binary cements - Nakanishi, Erika Y.; Frias, Moises; Santos, Sergio F. [UNESP]; Rodrigues, Michelle S.; la Villa, Raquel Vigil de; Rodriguez, Olga; Savastano Junior, Holmer (Elsevier B.V., 2016)
In recent years, agro-industrial residues are focusing attention worldwide as a new source of pozzolans; in Brazil one of the wastes generated from agro-industrial activities comes from elephant grass that is cultivated as biomass for energy cogeneration. The goal of this paper is to analyze the influence of elephant grass, once activated at 700 degrees C for 1 h in electric furnace, on the evolution of the hydration reaction as well as physical and mechanical properties in blended cement elaborated with 20% of elephant grass ash. For the present study, different instrumental techniques of characterization and methodologies (XRF, XRD, TG/DTG, mercury porosimetry, isothermal calorimetry and mechanical strength) were used. The results obtained in the present work show, that due to its high pozzolanic activity, the elephant grass ash activated at 700 degrees C can be used as an alternative pozzolan in the blended cement manufacture. Additions of 20% of ash confirm the formation of CSH gels and hexagonal C(4)AH(13) as main products from hydration as well as pozzolanic reaction. The 20% ash blended cement showed lower heat evolution than OPC and similar to the 20% silica fume blended cement, a 12% of reduction of compressive strength and an important reduction of pore sizes below 50 nm. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Elephant grass ash; Pozzolanic activity; Blended cement; Hydrated phases; Properties